Characterization of a selective surface based on chromium, iron and aluminum oxides for application in solar-thermal collectors - Dutra, Kaio Hemerson (2022)
The depletion of conventional energy sources and the concern with the environmental impacts of the use of fossil fuels sparked interest in researching new energy sources and improving existing processes. In this context, the solar energy presents itself as one of the most promising energy sources on the planet, given its wide availability and applicability in thermal processes. However, its use still represents a great technological and economic challenge, because many systems that use this energy still have low efficiency and high cost, which makes them uncompetitive in competition with systems using other energies. With that, the search for the improvement of the processes awakens the researches in more adequate and cheaper materials, which represents a great scientific potential in the evolution of these technologies. Thus, the present work proposes to obtain and analyze a selective surface for applications in solar-thermal collectors, using CRFO (compound formed by chromium and iron oxides), varying the percentage by weight, and then mixed with aluminum oxide. For the tests, an experimental bench was built to simulate a flat plate solar-thermal collector in real operating conditions. Some characterizations were carried out, such as: techniques scanning electron microscopy (SEM), infrared analysis and UV-VIS absorptivity determination, as well as the graphs with surface temperatures and with radiation during the tests in the Sun for the composite (CRFO and aluminum oxide) and for the commercial surface (MRTiNOX). With the results obtained, it was verified in the field test that one of the produced selective surfaces obtained a result of absorptivity of 0.94 and 0.0349 of emissivity, which is close to that of the commercial surface. The results were confirmed in the characterization by UV-VIS, which showed high absorptivity values in the visible light range.